The Relationship between Nepal and Japan: Diplomacy and Development - Shrestha, Sunil Babu (NCWA Annual Journal, 2023)
After learning that Japan had developed and made marvelous progress because of education development, the then reformist Rana Prime Minister Dev Shumsher decided to send eight Nepalese students with the spirit of "Let’s learn from the East". Later, the students sent to Japan during the Chandra Shumsher era became beneficial and effective not only for the transfer of knowledge, skills, and technologies; it has also helped to bud the relationship between Nepal and Japan. Later the diplomatic relation was established on September 1, 1965. Furthermore, the relationship between both nations has been strengthening through high-level exchange visits, people-to-people relationships, and development diplomacy. Japan has been helping Nepal in key sectors such as human resource development, health, agriculture development, infrastructure development, environment protection, culture, etc. through grants, loans and technical support This has made a great contribution to the socioeconomic development of Nepal. Nepal and Japan’s relationship is without any problems since the establishment of the relation between the two countries and put similar views on the international agenda in the United Nations (UN) and international platform based on the principles of peaceful coexistence, sovereign equality of the states, and non-alignment. In this context, this paper tries to advocate for the promotion and integration of science diplomacy to deepen ties between Nepal and Japan in the era of science and technology so that more long-term benefits could be achieved from Japan for the sustainable development of Nepal.